Library and information science: Past and future from an international perspective - Martínez-Ávila, Daniel (Anuario ThinkEPI, 2017)
Some of the historical and political aspects that have shaped Library and Information Science professions in Spain, and other countries such as Brazil and the United States, are reviewed. This paper aims to identify some of the key trends and to propose some contents that should be covered by graduate and undergraduate programs. I propose a greater emphasis on technology, ethics, critical theories, and research in LIS studies, as well as a closer collaboration with Journalism, Communication, and Computer Science.
Keywords: Library and Information Science; LIS; Education; Job market; Comparative research; Spain; Brazil; United States.